Remote Supervision of IV-tPA for Acute Ischemic Stroke by Telemedicine or Telephone Prior to Transfer to a Regional Stroke Center is Feasible and Safe - Pervez, Muhammad A (2009)
BACKGROUND: Due to a shortage of stroke specialists, many outlying or “spoke” hospitals initiate intravenous (IV) thrombolysis using telemedicine or telephone consultation prior to transferring patients to a regional stroke center (RSC) hub. We analyzed complications and outcomes of patients treated with IV tPA using the “drip and ship” approach compared to those treated directly at the RSC. METHODS: A retrospective review of our Get With the Guidelines Stroke (GWTG-Stroke) database from 01/2003-03/2008 identified 296 patients who received IV tPA within 3 hours of symptom onset without catheter-based reperfusion. GWTG-Stroke definitions for symptomatic intracranial (sICH), systemic hemorrhage, discharge functional status and destination were applied. Follow-up modified Rankin Score (mRS) was recorded when available. RESULTS: Of 296 patients, 181 (61.1%) had tPA infusion started at an outside spoke hospital (OSH) and 115 (38.9%) at the RSC hub. OSH patients were younger with fewer severe strokes than RSC patients. Patients treated based on telestroke were more frequently octogenarians than patients treated based on a telephone consult Mortality, sICH and functional outcomes were not different between OSH vs. RSC, and telephone vs. telestroke patients. Among survivors, mean length of stay was shorter for OSH patients but discharge status was similar and 75% of patients walked independently at discharge. CONCLUSIONS: Outcomes in OSH “drip and ship” patients treated in a hub-and-spoke network were comparable to those treated directly at an RSC. These data suggest that “drip and ship” is a safe and effective method to shorten time to treatment with IV tPA.